Changes of Divergence and Confluence Relationship Between Dongting Lake and the Yangtze River After the Operation of the Three Gorges Project and Its Impact on the Waterway Depth - Yang, Yunping; Liu, Wanli; Zhang, Jie; Yang, Lijie; Jia, Menglin; Zhu, Lingling (Frontiers in Earth Science, 2022)
This study choses the Dongting-Lake–Jingjiang confluence of the Changjiang River, since the operation of the Three Gorges Project, the split and sediment distribution of the three outlets of Dongting Lake—that is, Songzikou, Taipigkou, and Ouchikou—have continued to decrease. Along with the decreasing flow of Dongting Lake, the relative increase in the runoff of the Jingjiang reach and the increase in riverbed scouring intensity have increased the relative height difference between Jingjiang and Dongting Lake, intensifying the reduction of the split and sediment distribution of the three outlets. The riverbed scouring of the Jingjiang reach has created a promising foundation for an increase in the waterway dimensions. However, the length of the reach not meeting the requirements of 4.5 m× 200 m (water depth × width) is 18.4 km, of which the length in the river-lake confluence is 12.6 km, accounting for 68.35% of the total length of obstructed navigation. Furthermore, at the reach (Zhicheng–Dabujie reach) affected by the first outlet (Songzikou), a 4.5-m flume has been formed, but its width is less than 200 m; moreover, the “steep slope and rapid current” phenomenon is clear, and it affects the safety of ships. At the reach (Taipigkou reach) affected by the second outlet, the shrinkage of the bottomland, and the intersecting braided river channels make the low-flow routes unstable, the water depth being less than 4.5 m. At the reach (Tainxingzhou–Ouchikou reach) affected by the third outlet, the shoreline of the reach has collapsed and retreated significantly. Additionally, point bar scouring and the downstream movement of cut banks have caused the downstream waterway width at the reach to be reduced to less than 200 m or formed shoals with a water depth of less than 4.5 m. Owing to the jacking effect of the lake’s outflow backwater, the flow rate of the reach (Xiongjiazhou–Chenglingji reach) affected by the confluence of Dongting Lake decreased, creating a shoal with a water depth of less than 4.5 m in the navigation waterway.